HR Analytics: A Tool for Talent Management - Gupta, Megha; Srivastava, Nandini (International Journal of Psychosocial Rehabilitation, 2020)
This is a conceptual paper on HR analytics: the trend from traditional practices of managing people data to modern strategies of interpreting data to take vital talent management decisions with special reference to the hospital industry. The human resource function of the 21st century has become more competent with the finest application of technology developments. HR analytics is playing a key role in the current volatile situation wherein business expectations have increased for better productivity & output. This empowers better judgment for talent using employees’ statistics, unlike banking on associations & faith. HR dashboards enable establishments to chart HR metrics with the planned organization’s goal. It mainly concentrates on trends of talent hiring, forecasting future requirements of HR, and cultivating employee spirits and engagement. Analytics forms the basis for data elucidation to diagnose developments and take educative actions for gainful business operations. In this paper, the researcher has tried to highlight how HR analytics provides a multi-dimensional approach towards building competent talent management approaches. The assessor has consolidated views of various HR research and has concluded how HR analytics supports an organization in terms of its talent hiring, engagement, and retention in such a volatile and highly competitive environment. This paper appraises the significance of analytics in people functions and practices and its applicability in various sub-functions and how HR analytics have supported employers in their passage from simple MIS reporting to evidence-based predictive decision-making.